Optimizing the Use of e-Commerce as a Marketing Medium for Online Shop Businesses in the City of Medan - Safrin, Feby; Simanjorang, Feronica (LifeSciFi, 2023)
The internet is a familiar presence in society, offering a multitude of conveniences, including news access and business transactions. It enables people to easily obtain information without incurring significant costs and provides a platform for various types of information and news. Furthermore, it facilitates business opportunities, with marketing being a pivotal aspect. Online marketing, facilitated by e-commerce, is a key avenue enabled by the internet. E-commerce involves conducting business activities using online platforms. The growth of this e-commerce system is evident in the increasing number of users over the years. This research aims to analyze the e-commerce platforms employed as marketing tools by online shops in Medan City, as well as the strategies employed by businesses in leveraging e-commerce. Additionally, the study aims to identify the factors driving the use of e-commerce in online shop businesses in Medan City and examine the optimization techniques applied when utilizing e-commerce as a marketing medium. The research employs a descriptive method with a qualitative approach. The findings reveal that e-commerce plays a significant role as a marketing medium for online businesses, particularly in Medan City. It simplifies product marketing, expands the reach of businesses, saves time, and facilitates effective promotional activities.